A path analysis of diagnosis effectiveness leadership styles: Implementing organizational culture at the Indonesian ministry of religion - Yudiani, Ema; Istiningtyas, Listya; Meyrinda, Jesyia; Khosiyah, Siti; Rahman, Zaizul Ab (Jurnal Psikologi, 2025)
Background: Work culture is important to consider in achieving organizational goals optimally. A positive work culture has a positive impact on the organization, its internal elements, and the public, thereby helping to achieve organizational goals.Purpose: This study investigates the direct and indirect influences of leadership style, work climate, and daily spiritual experience on organizational culture, while also assessing the mediating role of transformational leadership within State Islamic Religious Higher Education Institutions (PTKIN) in Indonesia.Method: This study used path analysis to examine how leadership styles, work climate, and daily spiritual experience influence organizational culture in PTKIN, with a sample of 410 respondents.Findings: Transformational leadership (β = 0.519, t = 5.447, p = 0.000) and work climate (β = 1.897, t = 8.424, p = 0.000) have strong, positive effects on organizational culture, while daily spiritual experience has a significant negative effect (β = -0.660, t = 2.190, p = 0.032). Transformational leadership also mediates the relationship between work climate and organizational culture (β = 0.657, t = 3.195, p = 0.023).Implication: The findings of this study have implications for the development of effective leadership and the cultivation of a positive work climate in PTKIN to strengthen organizational culture.